Incorporating quality management system in the implementation of OBE at Faculty of Engineering, UPM - Noordin, Nor Kamariah; Jaafar, Mohd Saleh; Megat Mohd Noor, Megat Johari; Wagiran, Rahman; Abdul Aziz, Azlan; Osman, Mohd Rasid (2008)
This paper presents the implementation of outcome-based education in terms of course delivery, assessment and evaluation at the Faculty of Engineering, Universiti Putra Malaysia. The implementation was formalized based on the quality management system (QMS) of the Faculty, called Putra 3Q. The aspects of delivery, assessment and evaluation were looked at from lecturer’s point of view as well as the program coordinator or head of department’s perspective. Examples of delivery modes and assessment tools related to the type of delivery employed were discussed and presented.